2017
DOI: 10.1038/s41467-017-01126-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional gene silencing mediated by microRNAs is controlled by nucleoplasmic Sfpq

Abstract: There is a growing body of evidence about the presence and the activity of the miRISC in the nucleus of mammalian cells. Here, we show by quantitative proteomic analysis that Ago2 interacts with the nucleoplasmic protein Sfpq in an RNA-dependent fashion. By a combination of HITS-CLIP and transcriptomic analyses, we demonstrate that Sfpq directly controls the miRNA targeting of a subset of binding sites by local binding. Sfpq modulates miRNA targeting in both nucleoplasm and cytoplasm, indicating a nucleoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 70 publications
2
52
0
Order By: Relevance
“…PUM1, by binding to its target sites, has been shown to induce a local change in RNA structure, which, in consequence, exposes specific miRNA binding sequence within 3′-UTRs [41]. Sfpq, a functionally versatile DNA-and RNA-binding protein, preferentially binds to long 3′-UTRs harboring multiple copies of Sfpq-binding motifs and promotes, presumably by modulating the secondary structure of a miRNA target, optimal positioning of miRNA-loaded RISC [42]. Nevertheless, other RBPs, such as Deadend 1 [43,44], RNA-binding motif protein 38 [45] and coding region determinant-binding protein [46,47], may limit the accessibility of miRNA targets by competitive binding within mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…PUM1, by binding to its target sites, has been shown to induce a local change in RNA structure, which, in consequence, exposes specific miRNA binding sequence within 3′-UTRs [41]. Sfpq, a functionally versatile DNA-and RNA-binding protein, preferentially binds to long 3′-UTRs harboring multiple copies of Sfpq-binding motifs and promotes, presumably by modulating the secondary structure of a miRNA target, optimal positioning of miRNA-loaded RISC [42]. Nevertheless, other RBPs, such as Deadend 1 [43,44], RNA-binding motif protein 38 [45] and coding region determinant-binding protein [46,47], may limit the accessibility of miRNA targets by competitive binding within mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is accumulating evidence that some fraction of mammalian miRNAs may also execute important nuclear regulatory functions by controlling gene expression in the nucleus at both transcriptional and posttranscriptional levels, as well as by affecting alternative splice site selection (Roberts, 2014). In a set of elegant experiments, a significant fraction of miRNAs and several RISC components, including AGOs, have been identified to become located and functionally operative within the nucleus of human cells (Avivi et al, 2017; Bottini et al, 2017; Castanotto et al, 2018; Gagnon, Li, Chu, Janowski, & Corey, 2014; Ohrt et al, 2008; Sarshad et al, 2018; Weinmann et al, 2009). Nuclear localized miRNAs were found capable both to suppress and to stimulate transcriptional expression at distinct gene loci, involving direct and indirect interference pathways.…”
Section: Epigenetic Foundations Of Transcriptional Memorymentioning
confidence: 99%
“…We found that the combination of the mir-450b-3p and MTCH2 is 6mer and identi ed its binding region on the chromosome. Bottini et al veri ed the targeting relationship between the mir-450b-3p and MTCH2, through the Ago-CLIP experiment (21). To verify the relationship between the miR-450b-3p and MTCH2,we rstly examined the levels of miR-450b-3p and MTCH2 mRNA in testis by RT-PCR.…”
Section: The Protein Expressions Of Changes Of Mtch2 and Mitochondriamentioning
confidence: 99%